Foliar and soil N fertilization as a function of cropping behaviour of Royal Delicious apple (Malus domestica) - SINGH, DEEPIKA; BHATIA, H S; SHARMA, S D; SHARMA, N C; KUMAR, PRAMOD; KUMARI, NEELAM (The Indian Journal of Agricultural Sciences, 2019)
The key factor to obtain good yield and high fruit quality in apple (Malus domestica Borkh.) production is tree fertilization. The present study was planned with the objective to investigate the effect of soil applied N sources through foliar Urea sprays on morphometric growth traits, yield and fruit quality of apple cv. Royal Delicious. The trial was carried out on 28-year old trees raised on Crab apple Malus sylvestris (L.) Mill rootstock. Soil application of N sources, viz. Urea, calcium nitrate (CN), N:P:K (19:19:19) + Urea, N:P:K (12:32:16) + Urea and CAN + foliar Urea sprays at the levels of 840, 700 and 560 g N/tree were used. The effect of soil application of N sources and levels along with foliar Urea sprays on growth, production and fruit quality of apple recorded CAN + foliar Urea at 700 g N/ tree as the superior combination for optimum growth, fruit set and yield which was closely followed by CN + foliar Urea and Urea (soil) + Urea (foliar) application at 700 g N/tree. Whereas, fruit quality in terms of fruit size, weight, sugars and total soluble solids were improved with CAN + foliar Urea as well as CN + foliar Urea at 700 g N/tree.